Characterization of eucalyptus wood-derived biochar and its effects on hexazinone behavior in soil - Fernandes, Bruno Caio Chaves (2019)
Biochar is a product rich in carbon produced from pyrolysis of organic materials in an environment with limited oxygen or anoxic conditions. The pyrolysis temperature of material has a direct influence on the properties of biochar and, consequently, on its potential for agricultural and environmental use. In this research, the biochar characteristics of eucalyptus wood residues produced at different pyrolysis temperatures and their relationship with the behavior of herbicide hexazinone in soil were evaluated. Initially, biochars were produced at temperatures of 450, 550, 650, 750, 850 and 950 °C on the hydrogen potential (pH value), electrical conductivity (EC), ash content, yield, volatile matter (VM) content, elemental analysis, Fourier transform-infrared spectroscopy (FT-IR), X-ray diffraction, scanning electron microscopy (SEM), specific surface area (SSA) and micropore volume (MV) (by N2 adsorption) of eucalyptus wood-derived biochar. In the second stage, sorption/desorption experiments were executed using the batch equilibrium method, leaching in glass columns and distribution in biometric flasks with biochars produced between temperatures of 650 to 950 °C. The results showed a positive correlation of pyrolysis temperature with pH value, EC and elemental carbon, and a negative correlation with yield, MV, oxygen, elemental hydrogen, SSA, H/C, O/C and (O+N)/C ratios. The Principal component analysis showed that the highest polarity index (O+N/C), ash content, and N/C ratio associated with a low H/C ratio were the characteristics that had the greatest influence on increasing sorption, promoting a reduction in leaching and availability of hexazinone. The biochars produced at 850 and 950 °C obtained the highest sorption, reducing leaching by more than 80% and hexazinone availability by more than 46%. The addition of biochar was efficient in decreasing the mobility and availability of hexazinone in the soil, reducing the risk of environmental contamination of this herbicide. However, the lowest available amount of hexazinone in the soil can reduce the effectiveness of weed control in field conditions